A new animal model for Polygonum multiflorum Thunb-induced liver injury in rats and its potential mechanisms. Issue 4 (8th June 2015) - Fan, Xing; Wang, Jiabo; Xie, Lihua; Dong, Yansheng; Han, Gang; Hu, Dan; Liu, Yue; Yuan, Benli; Wang, Hemei; Wu, Chunqi; Xiao, Xiaohe; Ding, Rigao; et al.
Graphical Abstract: Abstract: Objective : Highly accepted animal models are of the greatest importance in studying drug-induced liver injury (DILI), especially for those induced by the traditional Chinese medicine- Polygonum multiflorum Thunb (Chinese name: He-Shou-Wu, PMT) because of the difficulties in successfully simulating an animal model that can match the characteristics shown in humans. This research aims to establish an early-warning animal model to investigate the potential mechanisms of DILI related to the toll-like receptor 4 (TLR4), and to verify the effectiveness of serum microRNA-122 as a candidate biomarker for DILI. Methods : 2 hours after LPS injection, rats were administrated with PMT for 7 consecutive days Qd. On the 2nd h, 14th h, 5th day and 8th day, serum samples were collected for an ALT/ALP test and TaqMan detection of the microRNA-122 expression. After weighing the organ to body ratio for each rat, liver samples were treated for histopathology observation and mTLR-4 detection by RT-PCR. Results : Comparing against a single administration with PMT, livers collected from animals pretreated with an LPS injection were injured to various extents and underwent hepatocyte degeneration. Meanwhile, the expression of liver mTLR4 and serum microRNA-122 increased significantly ( p < 0.05). Conclusions : Activated by LPS, this rat model of DILI for PMT was established successfully and its potential association with TLR4 was established. Serum microRNA-122 might be used as a candidate biomarker for PMT-DILI.